Necrotising soft tissue infection secondary to an incarcerated De Garengeot hernia - McElhatton, Claire P.; Lewin, Joel; Muduioa, Geoff (International Surgery Journal, 2023)
De Garengeot hernias are rare and can be difficult to diagnose pre-operatively. This case presented as a right groin abscess with necrotising soft tissue infection extending into the right thigh. At operation, a perforated appendix was found within the femoral canal with a distal loop of small bowel fistulating into the abscess cavity. On review of the literature, this is the first case to be reported describing this finding.